Hadith #2454 - Sunan Abi Dawud - Aisha bint Abi Bakr; Aisha bint Talha عائشة بنت طلحة بن عبيد الله التيمى; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Talha bin Yahya bin Talha طلحة بن يحيى بن طلحة; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: He who does not determine to fast before dawn does not fast.
Grade: Sahih

Hadith #4711 - Sunan Abi Dawud - Aisha bint Abi Bakr; Aisha bint Talha عائشة بنت طلحة بن عبيد الله التيمى; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Talha bin Yahya bin Talha طلحة بن يحيى بن طلحة (Sunan Abi Dawud)
Allah knows best about what they were doing.
Grade: Sahih

Hadith #5215 - Sunan Abi Dawud - Aisha bint Talha عائشة بنت طلحة بن عبيد الله التيمى; al-Minhal bin 'Amr al-Asadi المنهال بن عمرو الأسدي مولاهم الكوفي; Hassan ibn Ali bin Abi Talib; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Maysara bin Habib al-Nahdi ميسرة بن حبيب النهدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Uthman bin 'Umar bin Fars عثمان بن عمر بن فارس (Sunan Abi Dawud)
When Banu Quraizah capitulated agreeing to accept Sa’d’s judgement, the Prophet (ﷺ) sent a messenger to him. When he came riding on a white ass, the prophet (ﷺ) said: stand up to (show respect to) your chief, or he said : “to the best of you”. He came and sat beside the Messenger of Allah (May peace be upon him).
Grade: Sahih